Cancer treatment paradigms - Marsh, Sharon (Henry Stewart Talks, 2018)
Cancer basics, Staging, Treating cancer, Surgery, Radiation, Chemotherapy, Log-Kill Hypothesis, Hormone therapy, Targeted therapy, A companion diagnostic, Treatment resistance, The tumour genome, Reducing side effects, Palliative care